Overview of Oman Power Transmission System and Protection Schemes for Effective Energy Management in Smart Grid Operations - Al Omairi, Saif; Al Balushi, Marya; Okedu, Kenneth E. (Frontiers in Energy Research, 2021)
This article presents an overview of the transmission system and protection schemes employed in the national power grid of Oman. The technical design requirements considering the percentage of allowable limits for the different transmission voltage levels in the power grid of Oman were considered based on the electrical standards and grid codes of Oman. Also, the protection and fault requirements based on relay settings and backup protection were some of the factors considered in this study. More so, the power flow, peak, and off-peak voltage profiles of the main interconnection and Dhofar transmission systems were analyzed in detail, considering projections for 2021 and 2025, respectively, for effective energy management and smart grid operations. The current protection equipment of the power grid of Oman was evaluated, and some improvement schemes were proposed considering the implementation of the new technology for smart grid operation. The continuous investment in the transmission system of the Oman power grid and the use of updated protection technology would lead to the enhancement of the performance of the Oman transmission system to reach a high-level power transmission availability.